Resolution of Inferior Wall Ischemia after Successful Revascularization of LAD Lesion: The Value of Myocardial Perfusion Imaging in Guiding Management of Multi-vessel CAD - Chen, Chien-Cheng; Niu, Ya-Lei; Hung, Guang-Uei (Cardiology and Cardiovascular Medicine, 2017)
A 53-year-old male with history of hypertension and hyperlipidemia was presented with angina pectoris. Multi-slice CT coronary angiography showed severe stenosis in both left anterior descending coronary artery (LAD) and right coronary artery (RCA). Myocardial perfusion imaging (MPI) revealed extensive ischemia in apex, anterior, septal and inferior walls. Invasive coronary angiography revealed total occlusion in RCA and an 80% stenosis in LAD. Revascularization was performed for LAD first due to much severer ischemia than RCA on MPI. Follow-up MPI showed resolution of ischemia in both LAD and RCA territories, and the patient remained symptom-free during two years of follow-up.